Pathological gait in partial foot amputation versus peripheral neuropathy - Elabd, Omar M.; El Nahass, Bassem G.; Ibrahim, Mona Mohamed (Gait & posture, 2023)
Partial foot amputation (PFA) is a common surgical loss of part of either the forefoot or mid-foot. It is usually the sequel to a cascade of physiological foot dysfunction such as peripheral neuropathy (PN). The gait compensation mechanisms associated with these foot disorders aren’t well understood yet. The aim of the study was to evaluate pathological gait compensation mechanisms in PFA due to PN versus PN alone through a comprehensive gait analysis. Plantar pressure, GRF, load distribution, footprint length and area, foot progression angle, step length, percentage of double limb support, and stance time were measured on 53 participants assigned into two well-matched groups: (A) 25 subjects with healed unilateral PFA and (B) 28 subjects with PN without ulcer. The gait analysis was conducted at a self-preferred walking speed using the FREEMED baropodometric platform and FREESTEP software. The PFA group showed a significant decrease in load over the remaining toes and metatarsal heads compared to the PN group (p = .001 and p = .003, respectively). Conversely, the PFA group showed a significant increase in load over the mid-foot and peak plantar pressure during mid-stance (p = .007 and p = .016, respectively). All other measured variables showed no significant difference between the two groups (p > .05). Individuals with PFA and PN or PN alone tend to shift their body loads posteriorly and redistribute their loads to compensate for the insufficient support from the forefoot. The PFA group was worse than the PN group. Furthermore, the PFA may not be the primary cause of the altered gait but rather the underlying systemic disease. The PFA surgery only worsens the compensatory mechanism. •Individuals with PFA and PN or PN only receive insufficient support from their forefoot.•As a compensatory mechanism, they shift their weight posteriorly over the mid-foot.•This compensation increases the load over the mid-foot.•Individuals with PFA and PN or PN only are at risk of medial longitudinal arch collapse.•The systemic illness rather than the amputation causes this alteration in PFA gait.